Perancangan Rute Optimal Distribusi Kargo Bahan Bakar Minyak dengan Metode Brute - Force Untuk Meminimasi Biaya Konsumsi Bahan Bakar Minyak Perusahaan Pelayaran PT XYZ - Tiodora, Brissa; Poeri Suryadhini, Pratya; Nopendri, Nopendri (Dinasti Research, 2024)
TSP of fuel oil distribution using tankers, the projected route search often does not contain the most minimal mileage, which can lead to adverse results such as significant additional costs. This research analyzes four different routes using several iterative proposals to reduce travel distance, time, and fuel costs compared to actual conditions. Problem solving is carried out using the Brute-Force method which enumerates all permutation results. The analysis results show that all proposed iterations were able to provide significant reductions in all three aspects. The four research routes achieved optimization results of 21,7% compared to the actual route modeling. This optimization proves that the iterative methods applied can substantially improve operational efficiency. Therefore, the determination of the tanker route must consider all the possibilities required in determining the route. The optimal route created is expected to have a new model with the aim of minimizing fuel costs based on the smallest distance and time calculations.